Procedure for the obtaining by means of MFE of the thermal fields, deformations and residual tensions in welded unions - García Rodríguez, Yenei; Burgos Sola, José (Rev. Téc. Fac. Ing. Univ. Zulia, 2010)
The following work shows the steps to keep in mind through a procedure designed to apply the simulation of the welding by means of Methods of Finite Elements (MEF). The caused fields of temperatures for the welding were based on the properties of steel ASTM A-36, under conditions of strong constraint in unions to ends as in unions in T. takes in consideration aspects of the transfer of heat in state transient, as well as the variation of the properties of the material in function of the temperature (not lineal). They are shown in the results displacements, deformations and residual stress obtained in the simulation.